Preditores de sobrecarga profissional na pandemia: exposição ao coronavírus, saúde mental e trabalho em saúde - Mombelli, Janaina Maria Rodrigues [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
To analyze predictors of mental health workers' burden during the coronavirus pandemic. Method: Descriptive, exploratory, cross-sectional study with a quantitative approach. Data collected between October and December 2020 by means of a sociodemographic questionnaire and Scale of Evaluation of Overload of Professionals in Mental Health Services, in four services of a municipality in the state of São Paulo, Brazil, with 108 workers. Descriptive analysis and ordinary least squares multiple linear regression were performed in search of predictors for the variation in the scale score. Results: Median work overload (2.03) was evidenced. The predictors identified were: psychological or psychiatric follow-up, normal performance of activities during the pandemic, working directly with suspected or confirmed cases of COVID-19 and belonging to the risk group (p<0.05). Conclusion: Work conditions observed during the pandemic, simultaneously with workers' mental health care needs predict overload in health work.

Analisar preditores de sobrecarga dos trabalhadores de saúde mental durante a pandemia do coronavírus. Método: Estudo descritivo, exploratório e transversal, de abordagem quantitativa. Dados coletados entre outubro a dezembro de 2020 por meio de questionário sociodemográfico e Escala de Avaliação da Sobrecarga de Profissionais em Serviços de Saúde Mental, em quatro serviços de um município do estado de São Paulo, Brasil, com 108 trabalhadores. Análise descritiva e regressão linear múltipla de mínimos quadrados ordinários, em busca de preditores para a variação no escore da escala. Resultados: Evidenciou-se mediana sobrecarga de trabalho (2,03). Como preditores identificou-se: acompanhamento psicológico ou psiquiátrico, desempenho normal das atividades durante a pandemia, atuação direta com casos suspeitos ou confirmados de COVID-19 e pertencer ao grupo de risco (p<0,05). Conclusão: Condições de trabalho observadas durante a pandemia, simultaneamente com necessidades de cuidado à saúde mental dos trabalhadores predizem sobrecarga no trabalho em saúde. Descritores: Pandemias; Infecções por Coronavírus; Saúde mental; Profissionais de saúde.
Predictors of professional overload in the pandemic: coronavirus exposure, mental health and health work
Keywords: Pandemics; Coronavirus infections; Mental health; Health professionals; Pandemias; Infecções por Coronavírus; Saúde mental; Profissionais de saúde